Fostering Religious Moderation among Orphans and Disadvantaged Children in Jepara - Mundhir; M. Sihabudin; Nika Salma Rachim; Ali Imron (Dimas: Jurnal Pemikiran Agama untuk Pemberdayaan, 2025)
Religious moderation needs to be promoted at all levels of society, especially among adolescents, including orphans and the underprivileged. Jepara is one of the cities with a significant number of orphans and the disadvantaged. This study aims to instill the values ​​of Religious Moderation in orphans and the disadvantaged at the Orphan and the Underprivileged Educational Institutions in Jepara. The method employed is the Community-Based Research (CBR) model, utilizing a descriptive approach. The children were provided with participatory mentoring through training that included three stages: understanding the concept, internalizing the values, and implementing Religious Moderation in daily life. This activity was designed to increase participants' awareness and ability to apply attitudes of tolerance, justice, and respect for differences. The results revealed a significant increase in the understanding and practice of the values of Religious Moderation. Before the training, most participants situs toto did not fully understand this concept; however, after the mentoring, they exhibited positive changes in their social and religious behavior.